2000
DOI: 10.1128/aac.44.11.3163-3166.2000
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase Inhibitors with Activity against Rifampin-Resistant Mutants of Staphylococcus aureus

Abstract: A collection of rifampin-resistant mutants of Staphylococcus aureus with characterized RNA polymerase ␤-subunit (rpoB) gene mutations was cross-screened against a number of other RNA polymerase inhibitors to correlate susceptibility with specific rpoB genotypes. The rpoB mutants were cross-resistant to streptolydigin and sorangicin A. In contrast, thiolutin, holomycin, corallopyronin A, and ripostatin A retained activity against the rpoB mutants. The second group of inhibitors may be of interest as drug develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
90
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 26 publications
5
90
0
1
Order By: Relevance
“…This requirement is met by myxopyronin, corallopyronin and ripostatin, but resistance to the rifamycins confers cross-resistance to sorangicin. 182 The structural basis for the lack of cross-resistance to the three metabolites was recently revealed by an elegant study carried out by Arnold, Ebright and colleagues, 183 in which they elucidated in detail the binding interaction between myxopyronin and bacterial RNAP. The overall shape of both bacterial and eukaryotic RNAPs is reminiscent of a crab claw, wherein the two pincers define the active site cleft (Fig.…”
mentioning
confidence: 99%
“…This requirement is met by myxopyronin, corallopyronin and ripostatin, but resistance to the rifamycins confers cross-resistance to sorangicin. 182 The structural basis for the lack of cross-resistance to the three metabolites was recently revealed by an elegant study carried out by Arnold, Ebright and colleagues, 183 in which they elucidated in detail the binding interaction between myxopyronin and bacterial RNAP. The overall shape of both bacterial and eukaryotic RNAPs is reminiscent of a crab claw, wherein the two pincers define the active site cleft (Fig.…”
mentioning
confidence: 99%
“…It has also been observed that some rifampin-resistant mutations can confer sorangicin resistance, suggesting largely overlapping binding sites for these two drugs (31,127,145). However, the structures of these drugs are different and observation that some rifampin-resistant mutants are sorangicin sensitive, while most sorangicin-resistant mutations confer rifampin resistance, suggests that subtle differences exist with regard to their modes of action (145).…”
Section: Drug-resistant Rnap Mutantsmentioning
confidence: 99%
“…8B). More specifically, they are found in the protrusion, fork and external 1 and 2 domains of ␤ (14,31,81,82,97,108,120,127,129,130,156,160,174,178,186,201,202,207). Thus, these replacements most probably affect the conformation of the binding pocket and lower its affinity for rifampin.…”
Section: Drug-resistant Rnap Mutantsmentioning
confidence: 99%
“…Holomycin (4) also possessed antibacterial properties and provided moderate but broad antibiotic spectrum against 12 In addition, 4 showed the inhibition of RNA synthesis, 11 and the calculate log P (ClogP) did not exceed 2.0.…”
mentioning
confidence: 99%
“…11,12 In addition, 4 showed the inhibition of RNA synthesis, 11 and the calculate log P (ClogP) did not exceed 2.0. 13 These properties fascinated us to hybridize myxopyronins with the holothin molecule to expect the efficacy beyond our anticipations.…”
mentioning
confidence: 99%